Multinational Corporations’ Tax Optimization Strategies and European Union Policies - Krifa-Schneider, Hadjila; Sattar, Abdul (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2021)
Multinational companies avoid taxes through sophisticated tax optimization techniques, also known as aggressive tax planning (ATP). This paper serves two purposes: to understand these techniques and to analyze the factors that thwart efforts against ATP by taking the European Union (EU) as a case study. We use an analytic approach based on literature survey. We explain different ATP activities at micro and macro levels. We find that the EU has remained ineffective against tax avoidance due to the lack of legal competences and political will. Finally, we make some recommendations in the current functioning framework of the EU.